DAMPAK PERNIKAHAN JARAK JAUH TERHADAP KEHARMONISAN RUMAH TANGGA PERSPEKTIF ISLAM (Studi Kasus Di Desa Trimodadi Kecamatan Abung Selatan) - Kholifatun Qorifah; Taufik Kurohman; Mat Sahroni (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Many husbands and wives do not live together in the house because of work reasons that require them not to be able to live together temporarily. There is an example of a couple who has been in a long-distance marriage relationship, but the family has shown that they can still create a happy family, and show a harmonious and harmonious life. This research is qualitative research which is included in the type of field research and uses an empirical approach. The appropriate empirical approach is a qualitative descriptive approach in Trimodadi Village, South Abung District, North Lampung District. Long distance marriages are caused by two main factors, namely micro factors and macro factors. The conclusion that can be drawn is that participants consider the experience of living a long distance marriage as a challenge full of difficulties. Nevertheless, they view that everything they experience in a long-distance marriage is a test given by Allah SWT. In this context, commitment, religious beliefs, and love for children are determining factors in maintaining the sustainability of a long-distance marriage, even though the couple faces a number of challenges and difficulties in the process.